2021
DOI: 10.1097/nne.0000000000001120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of a School of Nursing Civility Team

Abstract: Background: Promoting civility in nursing education can be accomplished with civility teams, assessing perceptions of civility and developing initiatives to address areas needing improvement. Problem: There is a lack of information about the effectiveness of civility teams in nursing education, leading to uncertainty on how to develop and assess civility teams. Approach: This article discusses how 1 school of nursing implemented a civility team and used the Clark Healthy Work Environment Inventory to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…These norms refer to informal behavioral rules that address mutual respect generally accepted within a group (Laschinger and Read, 2016). Research has demonstrated that civility can increase efficacy at work, leading to a reduction in burnout among health-care employees (Bernard et al , 2022; Phan and Hampton, 2022). In the current and complex health-care environment, a renewed emphasis on the humanistic foundation of human caring brought about by authentic relationships could be instrumental in overcoming crises.…”
Section: Introductionmentioning
confidence: 99%
“…These norms refer to informal behavioral rules that address mutual respect generally accepted within a group (Laschinger and Read, 2016). Research has demonstrated that civility can increase efficacy at work, leading to a reduction in burnout among health-care employees (Bernard et al , 2022; Phan and Hampton, 2022). In the current and complex health-care environment, a renewed emphasis on the humanistic foundation of human caring brought about by authentic relationships could be instrumental in overcoming crises.…”
Section: Introductionmentioning
confidence: 99%